1993
DOI: 10.1002/pro.5560020813
|View full text |Cite
|
Sign up to set email alerts
|

Defensins promote fusion and lysis of negatively charged membranes

Abstract: Defensins, a family of cationic peptides isolated from mammalian granulocytes and believed to permeabilize membranes, were tested for their ability to cause fusion and lysis of liposomes. Unlike a-helical peptides whose lytic effects have been extensively studied, the defensins consist primarily of 0-sheet. Defensins fuse and lyse negatively charged liposomes but display reduced activity with neutral liposomes. These and other experiments suggest that fusion and lysis is mediated primarily by electrostatic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
98
2
5

Year Published

1994
1994
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 155 publications
(125 citation statements)
references
References 58 publications
20
98
2
5
Order By: Relevance
“…These observations suggest that cell membrane permeabilization is the main source of defensin activity in vivo. This is supported by the observations that defensins form voltage-dependent ion channels in planar bilayers (Kagan et al, 1990) and induce lysis of small sonicated lipid vesicles (Fujii et al, 1993). The work presented here investigates the mechanism of the permeabilization of large unilamellar vesicles by the human defensin HNP-2.…”
mentioning
confidence: 58%
See 4 more Smart Citations
“…These observations suggest that cell membrane permeabilization is the main source of defensin activity in vivo. This is supported by the observations that defensins form voltage-dependent ion channels in planar bilayers (Kagan et al, 1990) and induce lysis of small sonicated lipid vesicles (Fujii et al, 1993). The work presented here investigates the mechanism of the permeabilization of large unilamellar vesicles by the human defensin HNP-2.…”
mentioning
confidence: 58%
“…0.2 (SD) pM (18 experiments), whereas for rHNP-2, 50% leakage occurs at 0.07 pM rHNP-2. Fujii et al (1993) have also observed that reduced human and rabbit defensins are more active than the native forms. The gen- era1 features of defensin-induced leakage described here have also been observed for melittin (Schwarz et al, 1992) and the channel-forming peptide GALA (Parente et al, 1990).…”
Section: Leakage Of Vesicle Contentsmentioning
confidence: 85%
See 3 more Smart Citations